Biapenem: Clinical and Microbiological Characteristics and the Place of The New Carbapenem In The Treatment of Severe Infections In The Hospital. Clinical Pharmacologists' Point of View - S. V. YAKOVLEV; M. P. SUVOROVA (Антибиотики и Химиотерапия)
A new carbapenem antibiotic — biapenem — previously used only in Japan and Southeast Asia, was registered in Russia in 2021. The article analyzes the antimicrobial, pharmacokinetic, and clinical characteristics of biapenem in detail, provides pharmacodynamic justifications for antibiotic dosing. The most important properties and advantages of biapenem related to antimicrobial action (higher activity and eradication potential against Pseudomonas aeruginosa), the highest stability among carbapenems to carbapenemases of classes D (OXA-48-type) and B (NDM-type) are emphasized, which determines a new option for the treatment of infections caused by carbapenem-resistant Enterobacterales (biapenem in combination with polymyxin/colistin and/or tigecycline). Among the features of pharmacokinetics, it is necessary to highlight low albumin binding (3.7%), good tissue penetration, as well as stable pharmacokinetics of biapenem in patients in critical condition, septic shock, and those requiring renal replacement therapy. Pharmacodynamic modeling has established the most optimal dosage of biapenem in sepsis and septic shock: 300 mg (3-hour infusion) every 6 hours or 600 mg every 12 hours. A dosage regimen of 300 mg QID is preferable in patients undergoing continuous renal replacement therapy. The effectiveness of biapenem has been documented in numerous studies, which also show good antibiotic tolerability and safety: the frequency of side effects averaged 2% and was lower than that of other carbapenems. Biapenem can be effectively and safely prescribed to the most problematic elderly patients with serious comorbid conditions and impaired kidney and liver function.